LRINEC: an economical diagnostic tool for prognosis in patients with necrotizing soft tissue infections in a tertiary care centre - Prasad, Ballapalli Hari; Chengalrayan Narendra, Minchala; Hameed, Shaik Nurul (International Surgery Journal, 2019)
Background: The objective of the study was to evaluate the efficacy of LRINEC score in the management and prognosis of patients with soft tissue necrotizing infections. Methods: This is a prospective study conducted in Sri Padmavathi Medical College (W), Tirupati, Andhra Pradesh, India from May 2018 to January 2019. It included 50 patients who were diagnosed with severe soft tissue infection of lower limbs who needed surgical intervention. The effectiveness of LRINEC score was determined from the outcome. Results: Age group varied from 40 to 60 years. Out of 50 patients 40 were men and 10 were women. The male to female ratio was 4:1. All the patients were investigated at the time of admission in the emergency department using the LRINEC score. Hospital stay varied from 15-45 days. Conclusions: This study concludes that LRINEC score is an economical and accurate investigating tool in necrotizing soft tissue infections to determine the prognosis and outcomes.